Legal Protection for Online Transportation Service Drivers as Platform Workers in Indonesia - Dian hadiati (Yayasan Tranformasi Aksara Digital, 2024)
Lifting the issue of the absence of clear laws regulating partnership relations in this gig economy context, it puts partners like online transportation drivers in a vulnerable position where they lack alternative livelihoods due to the precariousness of the labor market, leading to job uncertainty and threatening their welfare. This research aims to find alternative policies that accommodate economic actors and driver partners. This paper is a normative juridical study, utilizing the legislative approach (Statutory Approach), conceptual approach (Conceptual Approach), and comparative legal approach (Comparison Approach). In practice, the agreements encountered are partnership agreements, but they do not place drivers on equal footing or subordinate terms. Therefore, this relationship needs to be transformed into a true partnership (mutualistic partnership) that does not disadvantage either party, even though the collaboration model is based on the gig economy model. The government needs to establish partnership cooperation standards as agreed upon by the parties, regarding rights, obligations, and social guarantees.